A Rasch Model Analysis in Measuring students' Critical Thinking Skills in science learning model Problem Based Learning (PBL) Based on Local Wisdom - Cahayu, Sri Anika; Siburian, Jodion; Hamidah, Afreni; Falani, Ilham (Pendidikan Kimia Unimus, 2024)
One of the skills that students must have in the 21st century is critical thinking skills. The learning model that can develop critical thinking skills is the model of problem-based learning (PBL). The purpose of this study is to measure the critical thinking skills of students in sciencelearning model problem-based learning (PBL) based on local wisdom using the Rasch model. The critical thinking skills test was given to 36 students of class VII A and VII B at SMP Negeri 6 Sungai Penuh. The samples in this study were divided into control and experimental classes selected through the purposive sampling technique. Data collection techniques used tests and observation sheets. The data obtained were analyzed through a quantitative descriptive approach using the help of the Rasch model program with Winsteps software. The study results explained that problem-based learning (PBL) of local wisdom can improve critical thinking skills on student learning outcomes with Rasch analysis. The unidimensional value indicates that the test measures one dominant variable, namely students' critical thinking skills, with a raw variance value of 42.3% (good) and a variance value of < 15% in the ideal test category. The results of the item reliability test using winstep indicate item reliability and person reliability of 0.44 and 0.45 with a Cronbach's alpha value of 0.91 (reliable). These results indicate that the items on the items are normal and valid in measuring students' critical thinking skills.